Preoperative Serum Albumin and C-Reactive Protein (CRP) as Predictors of Surgical Site Infection Following Laparotomy in a Low Resource Setting: A Prospective Cohort Study - Chimdiebele D. Nwosu; Ochonma A. Egwuonwu; Eric C. Ihekwoaba; Henry C. Okpara; Gabriel Chianakwana (International Journal of Medicine and Health Development, 2025)
Background: Postoperative surgical site infection (SSI) following laparotomy remains a problem of global concern with local studies reporting higher rates in comparison with more developed climes. Serum C-reactive protein (CRP) and albumin levels have been noted to play an important role in the peri-operative period. However, some controversy still exists on their role as SSI predictors in the preoperative setting. Objective: To determine the usefulness of preoperative serum levels of albumin and CRP as predictors of SSI in patients undergoing laparotomy at a tertiary healthcare center in Nigeria. Materials and Methods: This was a hospital-based prospective observational cohort study conducted at the general surgery units of the study center from June 2021 to June 2022. Results: Twenty-two (36.1%) patients developed postoperative SSI in this study. There was a significant difference in the preoperative albumin levels between the patients who developed SSI and those who did not (36.80 ± 9.11 vs. 42.83 ± 9.39; P = 0.018). Preoperative serum albumin showed a fair predictive accuracy with an area under the curve (AUC) of 0.68 (95% confidence interval [CI] = 0.54–0.82; P = 0.024). Preoperative serum CRP, however, showed no significant difference between both categories and equally displayed poor accuracy with an AUC of 0.50 (95% CI = 0.34–0.64; P = 0.89). Conclusion: Preoperative serum albumin was significantly associated with SSI and showed a fair predictive accuracy in forecasting the development of post-laparotomy SSI. Preoperative serum albumin levels remain a good, simple, and cost-effective tool to predict SSI in contaminated major abdominal surgeries. Preoperative serum CRP had only a limited application in this study cohort.